Study on the relationship among typhoon, weather change and acute ischemic stroke in southern Zhejiang Province of China - Yao Tong; Yating Chen; Yulong Yu; Faxing Wang; Lina Lin; Gangjian He; Lingyang Chen; Xiuxiu Zhuang; Wenwen Du; Yunchang Mo (BMC Neurology)
Abstract Objective This study aimed to investigate the relationship between the unique weather change and acute ischemic stroke (AIS) in the southern Zhejiang Province of China and to provide evidence for better predicting and preventing stroke. Methods We retrospectively collected 14,996 ischemic stroke patients data and weather data from January 2019 to December 2021 in the southern Zhejiang Province of China. The correlation and risk between meteorological factors and the number of AIS daily cases were calculated. Wilcoxon rank sum test was used to calculate the difference in the number of cases between typhoon-affected and non-affected periods. A prediction model obeying Poisson regression was established, and the accuracy of the correlation factors in predicting the number of cases was verified. Results In southern Zhejiang Province, the number of AIS was the highest in summer and the lowest in spring. Stroke onset is associated with temperature, water vapor pressure and typhoons (P < 0.05). The presence of typhoon (RR 0.882; 95% CI 0.834 to 0.933, P < 0.001) was a protective factor, while maximum temperature (RR 1.021; 95% CI 1.008 to 1.033, P = 0.043) and the water vapor pressure (RR 1.036; 95% CI 1.006 to 1.067, P = 0.036) were risk factors. The occurrence under the influence of typhoons was lower than that without the influence of typhoons (P < 0.05). The prediction model can predict the occurrence of stroke. Conclusion An association was observed between the occurrence of AIS, temperature, water vapor pressure and typhoon in the southern Zhejiang Province of China. Typhoon occurrence was associated with fewer cases. The predictive model may help high-risk populations prevent diseases early and assist hospitals in allocating resources promptly.